2016
DOI: 10.1088/1751-8113/49/17/17lt01
|View full text |Cite
|
Sign up to set email alerts
|

Slavnov and Gaudin–Korepin formulas for models withoutU(1) symmetry: the XXX chain on the segment

Abstract: Abstract. We consider the isotropic spin− 1 2Heisenberg chain with the most general integrable boundaries. The scalar product between the on-shell Bethe vector and its off-shell dual, obtained by means of the modified algebraic Bethe ansatz, is given by a modified Slavnov formula. The corresponding Gaudin-Korepin formula, i.e., the square of the norm, is also obtained.Introduction. The algebraic Bethe ansatz (ABA) [31,30] is a powerful technique to study the spectral problem of quantum integrable models, as we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
(86 reference statements)
1
15
0
Order By: Relevance
“…Another advantage with respect to the ABA approach concerns the fact that scalar products of separate states 4 can be generically expressed in the form of determinants, at least for rank one models 5 , [100, For z-oriented boundary magnetic fields, the model is solvable by ordinary Bethe Ansatz or by the q-vertex operator approach, and there exist exact representations for the correlation functions [27,28,63,64]. 2 Here we are referring not only to the Separation of Variables -the subject of the present article -but also to an interesting modification of the Bethe Ansatz (the so-called modified algebraic Bethe Ansatz), introduced in [65][66][67][68] and developed further in [69][70][71] in what concerns the computations of scalar products of Bethe states, a first step towards correlation functions. Let us also mention in this context the so-called off-diagonal Bethe Ansatz which was proposed to describe the spectrum of models without U(1) symmetry [72] (the corresponding eigenstates being anyway constructed through SoV).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another advantage with respect to the ABA approach concerns the fact that scalar products of separate states 4 can be generically expressed in the form of determinants, at least for rank one models 5 , [100, For z-oriented boundary magnetic fields, the model is solvable by ordinary Bethe Ansatz or by the q-vertex operator approach, and there exist exact representations for the correlation functions [27,28,63,64]. 2 Here we are referring not only to the Separation of Variables -the subject of the present article -but also to an interesting modification of the Bethe Ansatz (the so-called modified algebraic Bethe Ansatz), introduced in [65][66][67][68] and developed further in [69][70][71] in what concerns the computations of scalar products of Bethe states, a first step towards correlation functions. Let us also mention in this context the so-called off-diagonal Bethe Ansatz which was proposed to describe the spectrum of models without U(1) symmetry [72] (the corresponding eigenstates being anyway constructed through SoV).…”
Section: Introductionmentioning
confidence: 99%
“…Let us mention here that such inhomogeneous TQ-equations also appear naturally in the context of the modified algebraic Bethe Ansatz[65][66][67][68][69][70][71]133] 7. i.e.…”
mentioning
confidence: 99%
“…In 1998, Kitanine, Maillet and Terras [36] obtained this result by a different method and showed that the matrix elements of the matrix participating in the determinant representation of scalar products are expressed through derivatives of eigenvalues of the transfer matrix. Later similar results were obtained for models with the 6-vertex R-matrix with non-periodic boundary conditions [44][45][46][47]. In paper [48], a determinant representation was obtained for scalar products in the elliptic solid-on-solid (SOS) model, which is closely related to the 8-vertex model.…”
Section: Jhep06(2020)123mentioning
confidence: 61%
“…it has N zeros in the fundamental domain. The above properties imply that the dependence on x and y factorizes and the function φ (ν,µ) (v, r, x, y) can be represented in the form 47) where the function φ (ν,µ) 1…”
Section: Jhep06(2020)123mentioning
confidence: 99%
“…See[137] and also[138] for the original idea developed first for periodic chains and see also[20] for a first conjecture on these determinant formulae and[139][140][141] for previous determinant representations under special boundary constraints 7. One should notice that a priori the scalar products analyzed in[136] are between left C-gauged Bethe like states and right B-gauged Bethe like states so a priori different w.r.t.…”
mentioning
confidence: 99%